1999
DOI: 10.1111/j.1530-0277.1999.tb04287.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Confirmation of Quantitative Trait Loci Regulating Alcohol Consumption in Congenic Strains of Mice

Abstract: The QTL on chromosome 2 overlaps the 95% confidence interval of Alcp1 whereas that on chromosome 1 is new and has been called Alcp5. Marker-assisted selection was used in the N9 and subsequent generations to maintain the congenic lines and produce congenic strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…The NT system is involved in a number of processes including sensorimotor gating, nociception, and in the pharmacological responses to both therapeutic agents and drugs of abuse, and therefore QTL that impact these types of phenotypes could be detecting the same underlying genes as the QTL controlling the NT system. Four QTL impacting responses to intoxicating substances, Alcp4, Alcp25, Morph1, and Cocia4 reside on proximal chromosome 1 within the NTta QTL located there (Whatley et al, 1999;Bergeson et al, 2001;Gill and Boyle, 2003). The Morph1 QTL is related to morphine-induced antinociception, the Alcp QTL are involved in gender-specific alcohol preference and Cocia4 impacts psychomotor stimulant effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…The NT system is involved in a number of processes including sensorimotor gating, nociception, and in the pharmacological responses to both therapeutic agents and drugs of abuse, and therefore QTL that impact these types of phenotypes could be detecting the same underlying genes as the QTL controlling the NT system. Four QTL impacting responses to intoxicating substances, Alcp4, Alcp25, Morph1, and Cocia4 reside on proximal chromosome 1 within the NTta QTL located there (Whatley et al, 1999;Bergeson et al, 2001;Gill and Boyle, 2003). The Morph1 QTL is related to morphine-induced antinociception, the Alcp QTL are involved in gender-specific alcohol preference and Cocia4 impacts psychomotor stimulant effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…In most ethanol preference QTL studies, ∼2-3-month-old mice were phenotyped (Phillips et al 1994;Belknap et al 1997;Gill et al 1998;Tarantino et al 1998;Whatley et al 1999), although sometimes up to 9-month-old mice were used (Peirce et al 1998). Here, we used ∼7-month-old mice, so this also may have contributed to the different loci detected compared with the other studies.…”
Section: Alcohol Consumption Qtl In Micementioning
confidence: 99%
“…Of the three significant linkages identified in this study, only one, on distal chromosome 4, also was found to be linked to ethanol intake in the previous studies . The suggestive linkage on chromosome 2 (3% and 10% ethanol preference) may be equivalent to Alcp1/Pref2 (Phillips et al 1994(Phillips et al , 1998Melo et al 1996;Belknap et al 1997;Whatley Figure 5 Significant linkages. Left panels show results of interval mapping.…”
Section: Alcohol Consumption Qtl In Micementioning
confidence: 99%
See 1 more Smart Citation
“…A third line of evidence for a substantial genetic contribution to alcohol dependence comes from animal research. In selectively bred rodent lines, a considerable proportion of heritability in the development of addiction-related behavior has been observed, including strong preference for alcohol over water, willingness to work for alcohol, sensitivity to the hypnotic or activating effects of alcohol and to withdrawal, and demonstrations that alcohol is rewarding even in the presence of food and water [22,23,24,25,26]. A fourth line of evidence comes from early genetic studies in humans that demonstrated genetic variations in genes related to alcohol metabolism that affect the predisposition to alcohol dependence [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%